Pengaruh Kompensasi, Motivasi Kerja, dan Metode Mengajar terhadap Produktivitas Kerja Guru Sertifikasi Pada SMP Negeri Kecamatan Trimurjo Tahun Pelajaran 2012/2013 - Pristia Winda Pratiwi; Samsi Samsi; Nurdin Nurdin (FKIP Unila, 2013)
This research is purposed to identified whether or not there is influence between compensation, work motivation, and teaching method to sertificated teacher work productivity in the state junior high school of Trimurjo district in academic year of 2012/2013. In doing this study, the writer used descriptive verificative method with ex post facto and survey approach. The technique sampling that writer applied is probability sampling with simple random sampling. From the analyses of the study is found that (1) there is influence of compensation to sertificated teachers work productivity of the state junior high school of Trimurjo district in academic year 2012/2013 about 39,1%. (2) there is influence of work motivation to sertificated teachers work productivity of the state junior high school of Trimurjo district in academic year 2012/2013 about 27,1%. (3) there is influence of teaching method to sertificated teachers work productivity of the state junior high school of Trimurjo district in academic year 2012/2013 about 34,4%. (4) there is influence of compensation, work motivation, and teaching method to sertificated teachers work productivity of the state junior high school of Trimurjo district in academic year 2012/2013 about 58,7%. Keyword : Compensation, Work Motivation, Teaching Method, and Sertificated Teachers Work Productivity